2018
DOI: 10.1007/s10916-018-0973-y
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Patient-Clinician Interface of Clinical Trials through Health Informatics Technologies

Abstract: The current state of clinical trials underscores a need for timely interventions to reduce the cost and length of the average trial. Newly developed health informatics technologies-including electronic health records, telemedicine systems, and mobile health applications-have recently been employed in a wide range of clinical trials in an effort to improve different aspects of the clinical trial process. The current review will focus on the observed benefits and drawbacks of using such technology to improve var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“… Philipp Bruland 2016 [ 18 ] Germany To determine the most commonly used data elements in clinical trials and their availability in hospital EHR systems. Jake Carrion 2018 [ 19 ] USA To examine the observed benefits and drawbacks of using Electronic Health Record (EHRs) to enhance various patient-centered aspects of the clinical trial process, specifically its potential to improve patient recruitment, patient retention, and data collection GeorgesDe Moor 2015 [ 20 ] Belgium To describe the EHR4CR project which aims to demonstrate a scalable, widely acceptable and efficient approach to interoperability between Electronic Health Record (EHR) systems and clinical research systems. Peter J. Embi 2005 [ 21 ] Ohio To determine if the use of EHR-based Clinical Trial Alert (CTAs) could enhance physicians’ participation in subject recruitment and increase physician-generated recruitment rates for an ongoing clinical trial.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Philipp Bruland 2016 [ 18 ] Germany To determine the most commonly used data elements in clinical trials and their availability in hospital EHR systems. Jake Carrion 2018 [ 19 ] USA To examine the observed benefits and drawbacks of using Electronic Health Record (EHRs) to enhance various patient-centered aspects of the clinical trial process, specifically its potential to improve patient recruitment, patient retention, and data collection GeorgesDe Moor 2015 [ 20 ] Belgium To describe the EHR4CR project which aims to demonstrate a scalable, widely acceptable and efficient approach to interoperability between Electronic Health Record (EHR) systems and clinical research systems. Peter J. Embi 2005 [ 21 ] Ohio To determine if the use of EHR-based Clinical Trial Alert (CTAs) could enhance physicians’ participation in subject recruitment and increase physician-generated recruitment rates for an ongoing clinical trial.…”
Section: Resultsmentioning
confidence: 99%
“… Common data elements relevant to clinical trials were identified and their availability within hospital information systems were assessed. Jake Carrion 2018 [ 19 ] Improvement of patient recruitment, patient retention, and data collection through using the EHR. Leveraging EHR tools can enhance the way clinical trials are planned and executed.…”
Section: Resultsmentioning
confidence: 99%
“…The low adoption rate of standardized procedures and protocols for electronic health records platforms may lead to difficulties in coordinating research activities. 97 Electronic health records analysis use for drug hypersensitivity warrants further investigation. 98 Computerized physician order entry and mHealth facilitate real‐time identification of potential study subjects for clinical research.…”
Section: Ehealth For Academic and Clinical Researchmentioning
confidence: 99%
“…In the field of health informatics, electronic health records are used in a wide range of clinical trials, including for improvements of the patient‐clinician interface and data analysis. The low adoption rate of standardized procedures and protocols for electronic health records platforms may lead to difficulties in coordinating research activities 97 . Electronic health records analysis use for drug hypersensitivity warrants further investigation 98 .…”
Section: Ehealth For Academic and Clinical Researchmentioning
confidence: 99%
“…The healthcare delivery often defined by the concept that a network of clinicians rather than an individual clinician who offers the care for the patients. The failure or the success of the modern healthcare system is determined by the ability of these clinicians [1]. As the complexity within the domain of healthcare increases the varying process and also the clinician gets more difficult to be managed and also aligned that has resulted in increased risk for the patients and improper use of the available resources [1].…”
Section: Introductionmentioning
confidence: 99%